(untitled) (Journal of Science and Technology, 2024)
Background: Anaemia is a clinical condition that results in the reduction of haemoglobin levels in the body and affects 33% of women of reproductive age worldwide (about 613 million women between 15 and 49 years of age). In Ghana, the occurrence of anaemia is reported to be 66% in children between the ages of 6 and 59 months, and 42% among women of reproductive age. This study determined the prevalence and risk factors of anaemia among women of reproductive age at a Ghanaian University. Method: Two hundred and six non-pregnant women aged 15–40 years, randomly selected from Kwame Nkrumah University of Science and Technology, Kumasi, Ghana, participated in this cross-sectional study. Data on socio-demographics, anthropometrics, dietary diversity scores and information on monthly blood flow (menstruation) and anaemia awareness were collected. Haemoglobin (Hb) levels, oxygen saturation levels and malaria infection status were also determined. The relationships between the independent variables and anaemic status of the study participants were assessed using bi-variate analysis. Results: The overall anaemia prevalence was 67.5%, and the prevalence of mild, moderate and severe anaemia were 35.4%, 26.7% and 5.3%, respectively. About 56.8% of the participants had a high dietary diversity score, and more than half (57.8%) had a normal body mass index (18- 24.9kg/m2). There was no significant association between body mass index (p=0.430), dietary diversity score (p=0.711), oxygen saturation level (p=0.761) and anaemia. However, monthly blood loss significantly contributed to anaemia (p=0.047). Conclusion: This study has highlighted the high prevalence of anaemia among reproductive-age women. Body mass index, dietary diversity score and oxygen saturation level were not potential risk factors associated with anaemia. However, monthly blood loss was associated with anaemia. Due to the adverse consequences of anaemia on the health of reproductive women, proper interventions such as regular supplementation of the diet with iron and folate can be included to replenish blood loss.